A novel high-frequency planar converter with heterogeneous ferrites based on the matching co-firing technology. Issue 14 (15th July 2022) - Peng, Rui; Lu, Yongcheng; Shi, Liang; Li, Fuyu; Zhang, Qin; Wang, Xueying; Li, Yuanxun; Su, Hua; Zhang, Huaiwu
Abstract: The converter is an important component of integrated circuits. A novel planar converter was designed with heterogeneous ferrites (different permeability). The permeability of the ferrite distributed in the middle part and both ends of the planar converter is 70 and 500, respectively. Compared with the traditional converter, the designed one has a smaller size (4 mm × 4 mm × 0.55 mm), higher working frequency (3 MHz) and higher efficiency (91%). Co0.01 Ni0.39 Zn0.43 Cu0.17 Fe1.98 O4 (F70, permeability of 70) and Co0.01 Ni0.26 Zn0.56 Cu0.17 Fe1.98 O4 (F500, permeability of 500) ferrites were synthesised in our laboratory to fabricate such a heterogeneous planar converter. Bi2 O3 was used to modify the sintering mechanical properties of F70 and F500 ferrites and realise matching co-firing of these two materials. Bi2 O3 can coexist with both ferrites. A heterogeneous model was built based on the F70 + 0.8 wt%Bi2 O3 and F500 + 0.4 wt%Bi2 O3 ferrites, and the variations in geometry and stress were researched through finite element simulation. Simulation results indicate that matching co-firing of these two ferrites was achieved. The designed planar converter with a heterogeneous layer was fabricated with the F70 + 0.8 wt%Bi2 O3 and F500 + 0.4 wt%Bi2 O3 ferrites through the low-temperature co-fired ceramic technology. No crack and curving were observed at the heterogeneous interface, and the performance of the fabricated planar converter was consistent with that of the designed one. The quantification and simulation of sintering mechanical properties are promising methods to realise the matching co-firing of heterogeneous layers, which could promote the development of passive integration.